Reflecting on the Limits of Marxian Topography with Althusser and Negri - Viparelli, Irene (2018)
This article, starting from the specific question of the insufficiencies of the Marxian topography, will try to show that between the two theoretical dispositifs there is a relation of “proximity in difference”. On the one hand, both authors come to see an “ontological breakthrough” as the only way to refound revolutionary theory. On the other, their different views of historical temporality impose two contrasting “ontological solutions”. In the conclusion, I will present the hypothesis that there existsan “aporetical complementarity” between the two theoretical proposals, a privileged ground on which to extend the comparison of the two ontological proposals – aleatory materialism versus constituent ontology – formulated by the two authors in the early 1980s.